Policy discourses on irregular migration in Germany and the United Kingdom - Vollmer, Bastian A.; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Migration expert Bastian Vollmer explores the contentious issue of irregular migration in the highly-charged contexts of Germany and the UK. Through policy and discourse analysis the author explains why, despite the differing contexts and migration histories, German and British policy responses to the issue are now on a convergent path.
Keywords: Noncitizens -- Government policy -- Germany; Noncitizens -- Government policy -- Great Britain; Germany -- Emigration and immigration -- Government policy; Great Britain -- Emigration and immigration -- Government policy